PENGARUH REALISASI BELANJA PEMERINTAH TERHADAP KRIMINALITAS DI KOTA PEKANBARU MENGGUNAKAN PENDEKATAN ERROR CORRECTION MODEL (ECM) - Fajar Fadly (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2023)
This study aims to see how the relationship between government spending in Pekanbaru with the number of crimes in Pekanbaru. In this study government spending is used as an independent variable is in the field of education, economy, security and order as well as social protection. In this study using the method of Error Correction Model (ECM) to see the effect both in the long and short term of the regression equation used. Where to make sure there is a linkage in the equation the effect in the long term and short term (cointegration) on the variables of the study. It was found that there is a cointegration relationship and in the long run all independent variables have no real (significant) effect on crime in Pekanbaru. Whereas in the short term, only economic spending and social protection have a significant effect with negative economic correlates to crime and positive social protection correlates to crime.